2020
DOI: 10.1186/s12879-020-05486-6
|View full text |Cite|
|
Sign up to set email alerts
|

Risk conditions in children hospitalized with influenza in Norway, 2017–2019

Abstract: Background Norwegian children are more frequently hospitalized with influenza than adults. Little is known about the characteristics of these children. Our aim was to investigate the presence of pre-existing risk conditions and to determine the duration of influenza hospitalizations in children during two influenza seasons. Methods The Norwegian Patient Registry holds data on all hospitalized patients in Norway. We included all patients younger than 18 years hospitalized with a diagnosis of influenza during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
2
25
0
2
Order By: Relevance
“…A study based on The Norwegian Patient Registry revealed a decrease in the hospitalization rates among children with influenza the older the children were [ 9 ]. A similar trend was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study based on The Norwegian Patient Registry revealed a decrease in the hospitalization rates among children with influenza the older the children were [ 9 ]. A similar trend was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study based on data from 16 countries, which represented 79% of the population of America, the average pooled rate of influenza-related respiratory hospitalizations in children under 5 years of age amounted to 90 cases per 100,000 population [ 8 ]. A study based on the Norwegian Patient Registry showed the highest hospitalization rates in children aged under 6 months and a drop in the number of hospitalization cases the older the children were [ 9 ]. A systematic review and meta-analysis made in China showed the highest rates of hospitalization related to influenza in the group of children at the age of <5 years, and thus this group was considered to significantly contribute to influenza-related morbidity and mortality burden [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, children with heart diseases aged 0-4 years have a 6.2 greater odds, and those aged 5-9 years have a 30.6 greater odds of being hospitalized for influenza. 21 When admitted to the hospital for influenza, such children are at significantly increased risk for in-hospital mortality, acute respiratory failure, acute kidney injury, need for invasive and noninvasive mechanical ventilation, myocarditis, and need for extracorporeal membrane oxygenation. 22 Understandably, this corresponded with a higher length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], an error was identified in one author’s affiliations: Dr. Siri Helene is also affiliated to the Department of Biostatistics, Oslo Centre for Biostatistics and Epidemiology, Institute of Basic Medical Sciences, University of Oslo, Oslo, Norway.…”
mentioning
confidence: 99%